2021
DOI: 10.3390/cells10030714
|View full text |Cite
|
Sign up to set email alerts
|

HPV and Other Microbiota; Who’s Good and Who’s Bad: Effects of the Microbial Environment on the Development of Cervical Cancer—A Non-Systematic Review

Abstract: Cervical cancer is responsible for around 5% of all human cancers worldwide. It develops almost exclusively from an unsolved, persistent infection of the squamocolumnar transformation zone between the endo- and ecto-cervix with various high-risk (HR) human papillomaviruses (HPVs). The decisive turning point on the way to persistent HPV infection and malignant transformation is an immune system weakened by pathobionts and oxidative stress and an injury to the cervical mucosa, often caused by sexual activities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 197 publications
0
9
0
Order By: Relevance
“…HPV infection is a pathogenic factor of cervical cancer and other cancers, but its mechanism is still unclear [ 6 ]. At the same time, some studies have shown that not all HPV infections lead to cervical cancer, which suggested that in addition to HPV infection, cervical cancer also involves other factors such as genetics and environment [ 7 , 8 ]. In the 30 years since the cervical cancer screening programme was introduced, both cervical cancer incidence and death rates have fallen by more than 50% [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…HPV infection is a pathogenic factor of cervical cancer and other cancers, but its mechanism is still unclear [ 6 ]. At the same time, some studies have shown that not all HPV infections lead to cervical cancer, which suggested that in addition to HPV infection, cervical cancer also involves other factors such as genetics and environment [ 7 , 8 ]. In the 30 years since the cervical cancer screening programme was introduced, both cervical cancer incidence and death rates have fallen by more than 50% [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lactobacilli spp. increase adenosine and cytosine levels and reduce inflammation 65 , but they are suppressed in msAV and BV cases. Vaginal microbiome called community state type IV with decreased number of Lactobacilli spp.…”
Section: Discussionmentioning
confidence: 92%
“…A persistent infection with the high-risk HPV types 16 and 18 during pregnancy was, independent of cervical treatment, associated with an increased risk of PTB (aOR 3.72 [95% CI 1.47–9.39]). Both HPV persistence and PTB share some risk factors like an inflammatory vaginal milieu due to bacterial vaginosis, aerobic vaginitis and cervicitis following infection with chlamydia trachomatis 10 20 21 22 23 24 25 26 . Therefore, it remains unclear if the HPV infection is directly causal for the increased risk of PTB or if it is only an indicator for a high-risk milieu.…”
Section: Discussionmentioning
confidence: 99%